The Correlation of Smartphone Use Intensity with Aggressive Behavior in Early Childhood at TKIT Bina Insani (Kindergarten) - Komalasari, Mala; Yudha, Rivo Panji (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to analyse the relationship between the intensity of smartphone use and children's aggressive behaviour at Bina Insani IT Kindergarten, Serang Regency. This research uses descriptive correlation statistics with a quantitative approach. The sampling technique used in this study is a saturated sampling technique found in Non-Probability Sampling. The data collection technique is a questionnaire on the intensity of smartphone use and aggressive behaviour and photos of questionnaire filling activities. While the analysis technique used is using Pearson Product Moment using SPSS. The results in this study show a correlation coefficient value of 0.578, which indicates that the relationship is unidirectional and strong. Based on the results of the significance value between the variables of intensity of smartphone use and aggression, the significance value is 0.003 <0.05, which means that there is a significant correlation. So it can be concluded that the intensity of smartphone use with aggressive behaviour affects behaviour in Bina Insani IT Kindergarten.